Executive function and physical activity in preschool children from low-income settings in South Africa - Cook, Caylee Jayde (Department of Human Biology, 2020)
Executive function (EF), that shows rapid development in the preschool years, is foundational for cognitive development. Previous research has found aspects of physical development including gross motor skills and physical activity to be related to EF. However, evidence for these relationships in the preschool years, as well as in low- and middle-income countries is lacking. Therefore, this study aimed to investigate the relationships between EF (and related components of cognitive development) with physical activity and gross motor skills (GMS) in a sample of preschool children from urban and rural low-income settings in South Africa. Cognitive and physical outcomes were measured in a sample of preschool children (N=129; Mage = 50.7±8.3 months; 52.7% girls) from urban (Soweto) and rural (Bushbuckridge) low-income settings in South Africa. Cognitive components included EF, self-regulation (Early Years Toolbox, EYT), attention (adapted visual search task) and school readiness (Early Childhood Development Criteria Test). Physical outcomes included objectively measured physical activity (accelerometry), gross motor skills (Test for Gross Motor Development 2) and anthropometric measurements (height and weight). On average, children from both settings showed higher than expected scores for EF and self-regulation (based on Australian norms for the EYT), adequate gross motor proficiency and high volumes of physical activity (M total physical = 476 minutes per day). In contrast, a high proportion of children, particularly in the rural setting, demonstrated below average scores for school readiness. Investigations into the relationships revealed that EF was positively associated with self-regulation, attention and school readiness. Positive associations were also found between GMS and physical activity and, and physical activity and body mass index (BMI). And finally, that GMS, but not physical activity, was positively associated with all components of cognitive development. This study is the first to provide evidence for the importance of EF and the link between motor and cognitive development in preschool children from South African, low-income settings. Another key finding was that there may be factors promoting early EF skills in these settings but that these skills, although associated, are not transferring to school readiness. The lack of (or negative) associations between physical activity and cognition presents another key finding, further research is needed to identify whether there are specific amounts and types of physical activity that specifically benefit cognitive development.